Potensi Penambahan Pasir Bentonit Pada Tanah Lempung Untuk Stabilisasi Tanah - Munirwan, Reza Pahlevi (Universitas Iskandar Muda, 2023)
In civil engineering projects, soil must possess adequate bearing capacity to be utilized as a building material and as a construction material for soil-based structures. One effective approach for enhancing the load-bearing capacity of soil is the utilization of soil stabilization techniques. The improvement of the load-bearing capacity of clay soils can be achieved through the application of chemical stabilization techniques such as by using bentonite sand. The objective of this research is to investigate the effect of using bentonite sand as a stabilizing agent on the compaction parameter of clay soil. The experimental testing conducted in this study follows the guidelines outlined by the ASTM standard. Additional modifications were implemented on bentonite sand at concentrations of 2%, 4%, and 6%. The results of incorporating bentonite sand into the clay soil were evaluated in terms of the maximum dry density (MDD) and optimum moisture content (OMC) values. In general, the addition of bentonite sand to clay soil results in an increase in the maximum dry density (MDD) and optimum moisture content (OMC) values.